Network Externality as a Mediator on Business Growth:: An Empirical Study of Multilevel Marketing Industry in Indonesia - Furinto, Asnan; Selamet, Thamrin; Heriyati, Pantri; Mursitama, Tirta Nugraha; Ichsan, Mohammad (Journal The Winners, 2023)
The Multilevel Marketing (MLM) business became a more dynamic and competitive environment that drove companies to be sustainable in their business. However, the practices were sometimes perceived to be challenging by some of them. The research aimed to determine the role of network externality on Business Growth in the network marketing industry, often called MLM industry. With a non-probability sampling approach, the data were collected using structured questionnaires that were sent through emails or hardcopy. The collected data were analyzed using the PLS-SEM method with SmartPLS software. The results reveal that network externalities fully mediate both digital adoption capabilities and strategic agility to sustainable business growth. Meanwhile, network externality partially mediates the perceived product advantage to sustainable business growth. The result shall be taken into action by the companies as a key strategy in performing their business.